DETERMINANT FACTORS OF THE COMPANIES TO DO TAX AVOIDANCE - Ardillah, Kenny (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract” Tax avoidance is carried out by companies to minimize tax payments to the state by doing thin capitalization, transfer pricing, and earnings management because paying taxes is considered a burden and can reduce a company's profit. The objective of this research is to determine the effect of firm size, thin capitalization, transfer pricing, and earning management on tax aggressiveness with profitability as control variable. This research provide new evidence regarding the influence of firm size, thin capitalization, transfer pricing, and earnings management on tax avoidance in manufacturing companies with consumer goods subsector in Indonesia. The population in this research are all manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2017-2021. The data collection technique was using purposive sampling technique to determine research sample for five years period. This research uses the panel data regression method with a random effects model approach. The research results show that firm size and thin capitalization has a positive effect on tax avoidance, while transfer pricing and earnings management do not affect tax avoidance. From this result of research, the company management needs to increase awareness to comply with paying taxes and not to do tax avoidance practices. Keywords: Earnings Management; Firm Size; Tax Avoidance; Thin Capitalization; Transfer Pricing